Nonlocal multipoint problem for a differential equation of 2n-th order with operator coefficients - Baranetskij, Ya.O.; Demkiv, I.I.; Solomko, A.V.; Sus', O.M. (Carpathian Mathematical Publications, 2021)
In the article, the spectral properties of a multipoint problem for a differential operator equation of order 2n are studied. The operator of the problem has an infinite number of multiple eigenvalues. Each multiple eigenvalue corresponds to a finite set of root functions. A commutative group of transmutation operators is constructed. Each element of the group corresponds to the isospectral perturbation of the problem operator with antiperiodic conditions. The conditions for the existence and uniqueness of the solution are established for the selected family of multipoint problems, and this solution is constructed too.